2021
DOI: 10.1111/jnc.15290
|View full text |Cite
|
Sign up to set email alerts
|

Bile‐duct ligation renders the brain susceptible to hypotension‐induced neuronal degeneration: Implications of ammonia

Abstract: Hepatic encephalopathy (HE) is a debilitating neurological complication of cirrhosis. By definition, HE is considered a reversible disorder, and therefore HE should resolve following liver transplantation (LT). However, persisting neurological complications are observed in as many as 47% of LT recipients. LT is an invasive surgi-How to cite this article: Clément M-A, Bosoi CR, Oliveira MM, Tremblay M, Bémeur C, Rose CF. Bile-duct ligation renders the brain susceptible to hypotension-induced neuronal degenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
(92 reference statements)
4
7
0
Order By: Relevance
“…Supporting the results of our study, Clément et al. 50 recently demonstrated that in HE the brain, which is already compromised (decreased oxygenation and metabolic dysregulation), becomes susceptible to hypotensive insults resulting in neuronal cell death. Treating BDL rats with OP, which as we have shown here improves brain oxygenation, protected the brain against hypotension-induced neuronal cell degeneration.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Supporting the results of our study, Clément et al. 50 recently demonstrated that in HE the brain, which is already compromised (decreased oxygenation and metabolic dysregulation), becomes susceptible to hypotensive insults resulting in neuronal cell death. Treating BDL rats with OP, which as we have shown here improves brain oxygenation, protected the brain against hypotension-induced neuronal cell degeneration.…”
Section: Discussionsupporting
confidence: 91%
“… 49 Additionally, neuropsychological data were not collected from the subjects in the present study; however, this has been detailed in several previous publications, 10 , 29 including the effect of OP on cognitive performance in the BDL model. 50 In this study, we observe brain hypoperfusion at time points corresponding to previous reports of cognitive task performance impairment. 10 , 29 We rely on the logical extension that a reduction in availability of metabolic substrates will lead to neuronal dysfunction manifesting neuropsychological impairment.…”
Section: Discussionsupporting
confidence: 67%
“…Very similar abnormalities have been described in some case reports in HE, but their pathogenesis was unclear (4). We hypothesize that cortical hypersignals on brain MRI in HE are related to decreased cortical oxygenation, mediated by hyperammonemia as described by Hadjihambi et al (1), potentially compromising brain energy metabolism as previously shown by us and others (5,6). We would like here to outline that brain lesions were reversible in our case with a strict control of ammonemia, together with control of the bleeding and symptomatic ICU management.…”
supporting
confidence: 65%
“…, 1 potentially compromising brain energy metabolism as previously shown by us and others. 5 , 6 We would like to outline that brain lesions were reversible in our case with strict control of ammonemia, together with control of bleeding and symptomatic ICU management.…”
mentioning
confidence: 92%
“…The perikaryon of neuronal cells contains a high number of endoplasmic reticula with rRNA that is stained by cresyl violet ( Supplementary Figure 1 ). Cresyl violet is a commonly used stain to identify neurons (e.g., Coyle and Schwarcz, 1976 ; Ahmed et al, 2018 ; Mehrabadi and Sadr, 2020 ; Clément et al, 2021 ) and we diluted it in 50% ethanol in diethylpyrocarbonate-treated (DEPC) water, combined with an alcoholic dehydration of the tissue sections using ethanol diluted in DEPC water, to preserve the RNA integrity. Staining solutions were prepared in RNase free conditions and kept on ice.…”
Section: Methodsmentioning
confidence: 99%